Effect of Activator Type on Activated Carbon Characters from Teak Wood and The Bleaching Test for Waste Cooking Oil - Sriatun Sriatun; Shabrina Herawati; Icha Aisyah (Jurnal Rekayasa Kimia & Lingkungan)
The starting material for activated carbon was biomass from teak woodcutting, which consists of 47.5% cellulose, 14.4% hemicellulose, and 29.9% lignin. The surface area and iodine number of activated carbons are the factors determining the adsorption ability. This study aims to determine the effect of the activator type on activated carbon characters and test the absorption ability for waste cooking oil. The synthesis stages include carbonization, chemical activation, and then physics activation. The activation process consists of two steps. Firstly, the chemical activation via adding H2SO4, and H3PO4 at room temperature for 24 hours, the second, physical activation by heating at various temperatures of 300, 400, and 500 °C for two hours. The characterizations of activated carbon include water content, ash content, iodine number, functional groups, and surface area. Furthermore, the activated carbon was used as an adsorbent for waste cooking oil for 60 minutes at 100 °C with a stirring of 500 rpm. The results were analyzed using UV-Vis spectrophotometry at a maximum wavelength of 403 nm. The iodine numbers of activated carbon ranged 481.1-1211.4 mg/g and 494.8-1204 mg/g for H3PO4 and H2SO4, respectively.Activated carbon with H3PO4 of 15% and an activation temperature of 400 °C has the highest surface area of 445.30 m2/g.  The H2SO4 dan H3PO4 activators can be used to improve the quality of activated carbon in absorbing dyes in waste cooking oil, where the optimum concentration is 10-15% (v/v). The H3PO4 activator tends to produce a higher bleaching percentage than H2SO4.